Reducing The Operational Stop Time of Hauller Komatsu Hd465-7 by Using the Six Sigma’s Approach in PT X - Humiras Hardi Purba (Bina Nusantara University, 2016)
An operational stop time is a condition where heavy equipment is not working as usual. It is important to avoid this condition since excessive idling wastes an enormous amount of fuel and money. However, the operational stop time of a dump truck Hauller HD465-7 is 2.83 minutes, which is far above the normal standard. This project aims to optimize the improvement of an operational stop time by using a Six Sigma method with optimize plan selection. This will return the operational stop time to the standard range within 1.25 to 1.65 minutes. These steps of define, measure, analyze, improve, and control are applied to the standardization process according to the rules and criteria established by the Six Sigma. The result found that the Six Sigma’s approach which was applied in PT X has reduced the cost from US1,105,300 to US963,000 every month. An improvement have been made to matching fleet by combining six fleet of dump trucks at driving speed of 22 km per hour and the average simulated haul distance was 2,000 meters.